ANALYSIS OF THE FACTORS DETERINING MANY-YEAR CHANGES OF RUNOFF FROM OLIGOTROPHIC BOGS - Vladimir. I. Batuyev; Igor L. Kalyuzhniy (Водное хозяйство России: проблемы, технологии, управление)
The article presents results of the analysis of interaction of the factors determining the process of the winter and spring runoff formation on the basis of integrated hydro/meteorological observations at the Lammin-Suo (Leningrad Oblast) and ILass (Archangel Oblast) oligotrophic bogs during the period of stabilization (1950-980) and the period of climate change (1981-2018). We have stated that the freezing depth is a factor that regulates the ratio between the winter runoff and spring runoff. It has been shown that the layer of the winter runoff-forming moisture increase with its decrease and, consequently, the winter runoff is increasing while the spring runoff is decreasing. Analysis of results of the observation over the hydrological regime of the bogs of the north and north-west of Russia has shown that it is exactly the 1978-1980 period that is the boundary, which the freeze depth decrease and the change of the characteristics of runoff from bogs can be observed.